2011
DOI: 10.1021/es103925u
|View full text |Cite
|
Sign up to set email alerts
|

Use of Life Cycle Assessments To Evaluate the Environmental Footprint of Contaminated Sediment Remediation

Abstract: Ecological and human risks often drive the selection of remedial alternatives for contaminated sediments. Traditional human and ecological risk assessment (HERA) includes assessing risk for benthic organisms and aquatic fauna associated with exposure to contaminated sediments before and after remediation as well as risk for human exposure but does not consider the environmental footprint associated with implementing remedial alternatives. Assessment of environmental effects over the whole life cycle (i.e., Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 40 publications
0
74
0
Order By: Relevance
“…However, our results showed that strong sorption may also be achieved without activation but with the use of a high pyrolysis temperature (>700 C). In cases where nonactivated CM sorb almost as strongly as activated ones they may be preferential since they avoid energy input involved in the activation process, and are more favorable in the context of a complete life cycle (Sparrevik et al, 2011). However, it should be noted that the observed high sorption strength for some CM cannot be solely related to CM pyrolysis temperature since pyrolysis results in a series of complex reactions leading to less hydrophilic and more highly aromatic structure, and increased surface area and an increase in pore volume as pyrolysis proceeds.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed that strong sorption may also be achieved without activation but with the use of a high pyrolysis temperature (>700 C). In cases where nonactivated CM sorb almost as strongly as activated ones they may be preferential since they avoid energy input involved in the activation process, and are more favorable in the context of a complete life cycle (Sparrevik et al, 2011). However, it should be noted that the observed high sorption strength for some CM cannot be solely related to CM pyrolysis temperature since pyrolysis results in a series of complex reactions leading to less hydrophilic and more highly aromatic structure, and increased surface area and an increase in pore volume as pyrolysis proceeds.…”
Section: Discussionmentioning
confidence: 99%
“…Activated or nonactivated charcoals have been shown to reduce phytotoxicity of many herbicide residues and other chemicals in agricultural soils [Strek et al, 1981;Mukhin et al, 1995], reduce hydrophobic organic pollutant leaching , pollutant loss to the atmosphere [Bushnaf et al, 2011], and uptake from soil by plants [Vasilyeva et al, 2010;Jakob et al, 2012], and earthworms [Langlois et al, 2011]. However, replacing coalderived activated carbon with biochar is motivated by the successful use of coal-derived activated charcoals for the in-situ sequestration of hydrophobic organic compounds (HOCs) [Ghosh et al, 2011] and thus would reduce economic costs and improve the sustainability of remediation efforts [Sparrevik et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…This is in conformity with [7], stating that a certain degree of data quantity and accuracy are to be fulfilled for SMAA application. Dorini et al [3] and Sparrevik et al [32] suggest use of preliminary life cycle assessments (LCA) and economic analysis. A similar method of incorporating LCA results in MCDA has been applied by Prado-Lopez et al [33].…”
Section: Resultsmentioning
confidence: 99%